Different Temporal and Spatial Gene Expression Patterns Occur during Anther Development. - Koltunow, AM (1990)
We studied the temporal and spatial regulation of three mRNA sequence sets that are present exclusively, or at elevated levels, in the tobacco anther. One mRNA set accumulates in the tapetum and decays as the tapetum degenerates later in anther development. The second mRNA set accumulates after the tapetal-specific mRNAs, is localized within the stomium and connective, and also decays as these cell types degenerate during anther maturation. The third mRNA sequence set persists throughout anther development and is localized within most anther tissues. A tapetal-specific gene, designated as TA29, was isolated from a tobacco genome library. Runoff transcription studies and experiments with chimeric [beta]-glucuronidase and diphtheria toxin A-chain genes showed that the TA29 gene is regulated primarily at the transcriptional level and that a 122-base pair 5[prime] region can program the tapetal-specific expression pattern. Destruction of the tapetum by the cytotoxic gene had no effect on the differentiation and/or function of surrounding sporophytic tissues but led to the production of male-sterile plants. Together, our studies show that several independent gene expression programs occur during anther development and that these programs correlate with the differentiated state of specific anther cell types.